Bis(3-bromo-1-oxidoanthraquinone-κ2O1,O 9)-bis(pyridine-κN)copper(II) dihydrate - Ali, Hapipah Mohd; Ng, S.W.; Koushik, S.; Abdul Halim, S.N. (International Union of Crystallography, 2005)
The Cu atom in the title compound, [Cu(C14H6BrO 3)2-(C5H5N)2] ·2H2O, lies on a center of inversion; it is chelated by the bromo-substituted hydroxyanthroquinone molecule and is coordinated by the pyridine molecules in an all-trans octahedral geometry. © 2005 International Union of Crystallography Printed in Great Britain - all rights reserved.